2021
DOI: 10.1093/jac/dkab002
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of M184V/I mutation at the switch and at the time of virological failure of boosted protease inhibitor plus lamivudine or boosted protease inhibitor maintenance strategy (substudy of the ANRS-MOBIDIP trial)

Abstract: Background The ANRS12286/MOBIDIP trial showed that boosted protease inhibitor (bPI) plus lamivudine dual therapy was superior to bPI monotherapy as maintenance treatment in subjects with a history of M184V mutation. Objectives We aimed to deep analyse the detection of M184V/I variants at time of switch and at the time of virological failure (VF). Methods Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Baseline resistance testing is not recommended or performed before initiating ART in low and middle income countries, and, although transmitted resistance to integrase inhibitors is rare, surveillance is needed if dolutegravir is to be rolled out as first line treatment. In addition, there may be baseline HIV drug resistance to the other agents in two-drug regimens, namely lamivudine or emtricitabine, although existing data suggest that the presence of the most common resistance mutation to these drugs, M184V/I, does not seem to affect virological outcomes in those taking oral two-drug regimens 6566676869…”
Section: What Are the Considerations For Use In Resource-limited Sett...mentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline resistance testing is not recommended or performed before initiating ART in low and middle income countries, and, although transmitted resistance to integrase inhibitors is rare, surveillance is needed if dolutegravir is to be rolled out as first line treatment. In addition, there may be baseline HIV drug resistance to the other agents in two-drug regimens, namely lamivudine or emtricitabine, although existing data suggest that the presence of the most common resistance mutation to these drugs, M184V/I, does not seem to affect virological outcomes in those taking oral two-drug regimens 6566676869…”
Section: What Are the Considerations For Use In Resource-limited Sett...mentioning
confidence: 99%
“…However, most studies on two-drug regimens come from high-income settings.Baseline resistance testing is not recommended or performed before initiating ART in LMIC, and while transmitted resistance to INSTI is rare, surveillance is needed if dolutegravir is to be rolled out as first-line in LMIC. In addition, there may be baseline HIV drug resistance to the other agents in INSTI-based two-drug regimen, namely lamivudine or emtricitabine, although existing data suggest that the presence of the most common resistance mutation to these drug, M184V/I, does not appear to impact virological outcomes in those on oral twodrug regimens(60)(61)(62)(63)(64).Standard three-drug regimens contain tenofovir which has activity against Hepatitis B, preventing Hepatitis B viral replication and reactivation. Hepatitis B is not systematically screened for in low-income settings, and use of two-drug regimens may leave individuals with Hepatitis B coinfection sub-optimally treated for Hepatitis B, which may lead to compromise future treatment with entecavir.…”
mentioning
confidence: 99%
“…This question is crucial for dual therapies including 3TC, to accompany boosted darunavir or dolutegravir. The MOBIDIP study and its associated in-depth virological analysis suggested that an archived M184V mutation may not affect the viral efficacy of the darunavir/ritonavir/lamivudine two-drug therapy [6,41]. However, data are much less robust for the dolutegravir/lamivudine two-drug therapy, with a very limited number of patients included [8,9,42].…”
Section: Factors Associated With M184v Mutation Persistencementioning
confidence: 99%